Performance of Guava (Psidium guajava L.) Genotypes at Lower Hills of Nagaland - Talang, Hammylliende; Deka, B. K.; Aomi, Vinika K.; Rymbai, H.; Rajkhowa, D. J. (Indian Journal of Hill Farming, 2018)
Six guava genotypes of four years old viz. RCGH-11, RCGH-1, RCGH-4, RCGH-7, L-49 and Allahabad Safeda showed wide range of variation with respect to plant growth, yield and quality traits of fruit at lower altitudes of Nagaland. However, RCGH-1 was found superior in plant height (3.04 m), plant girth (35.17 cm) and canopy spread (3.64 m and 3.85 m in E-W & N-S direction) while RCGH-4 gives better fruit weight (171.28 g), fruitsize (6.23/6.97 cm length/diameter) and fruit yield (15.22 kg/tree). The hybrid RCGH-11 was found better in quality attributes like highest TSS (11.53 Â°Brix), total sugars (8.15%) and lowest acidity (0.40 %). The genotypes viz. RCGH-4 and RCG-11 were outscore othercultivars for growth, yield and quality attributes.